BS EN 3480. Aerospace series. Steel X6CrNiTi18-10 (1.4541). Air melted. Softened. Plate. 6 mm < a ≤ 50 mm. 500 MPa ≤ Rm ≤ 700 Mpa. (15th September 2020) - British Standards Institution,
No abstract available